Construction of ultrathin NiCo(HPO4)2·3H2O nanosheet with desirable inner boundary for hybrid supercapacitor. (April 2023) - Dong, Xin; Wu, Xiaowei; Li, Shizhen; Zhang, Zhanhui; Hu, Pu; Shang, Chaoqun
Abstract: The considerably theoretical electrochemical performance makes NiCo(HPO4 )2 ·3H2 O a potential electrode material for hybrid supercapacitor (HSC). Nevertheless, its practical application is impeded by the limited preparation process and undesirable structure, causing its incomplete utilization and unsatisfactory electrochemical performance. Herein, we rationally design a freestanding HSC electrode based on NiCo(HPO4 )2 ·3H2 O with the inner boundary to achieve its high utilization. The construction of an inner boundary can increase the ion transport channels and active sites during electrochemical processes. The freestanding NiCo(HPO4 )2 ·3H2 O-based electrode in three-electrode system delivers high specific capacitance (3005.1 mF cm −2 at 1 mV s −1 ) and favorable rate capability (2795 mF cm −2 at 10 mV s −1 ). When evaluated as a cathode and matched with the activated carbon anode, the asymmetrical HSC exhibits a specific capacitance of 2547.3 mF cm −2 (10 mV s −1 ) and desirable cycling stability after 4000 cycles (87 % capacitance retention). Graphical abstract: The construction of inner boundary in freestanding CC@NiCoPO-6/NiCoPO-6 electrode, which can provide more active sites and fast ion diffusion pathway during electrochemical reaction processes compared to that of CC@NiCoPO-12 with limited ion transport. Unlabelled Image Highlights: A freestanding supercapacitor electrode based on the inner boundary of NiCo(HPO4 )2 ·3H2 O achieves high utilization. The construction of an inner boundary can increase the ion transport channels and active sites during electrochemical processes. The asymmetric supercapacitor shows ideal cycling stability, with 87% capacitance retention after 4000 cycles at up to 100 mA cm -2 .